THE EFFECT OF USING THE SPIN-ASSISTED WATER (AUDITORY, INTELLECTUAL, REPETITION) LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES ON THE ETHICAL POLITICS MATERIAL IN GRADE X AT SMKN 2 PADANG: Pengaruh Penggunaan Model Pembelajaran AIR (Auditory,Intellectualy, Repetition) Berbantuan Spin Terhadap Hasil Belajar Peserta Didik Pada Materi Politik Etis Kelas X di SMKN 2 Padang - Liza Husnita; Meldawati; anastasya maharani anastasya maharani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research is motivated by the low learning outcomes of students in History, particularly in the Ethical Politics material, which is caused by the lack of variety of learning models and interactive media that can stimulate in-depth understanding and active student involvement. The purpose of this study is to analyze the effect of the implementation of the AIR (Auditory, Intellectual, Repetition) learning model assisted by SPIN media on improving student learning outcomes. The method used in this study is a quantitative method with a pretest-posttest design. The instruments used include multiple-choice objective questions. Data analysis includes validity, reliability, difficulty level, discrimination power, normality test, t-test, and N-Gain calculation. The results of the study indicate that there is a significant increase in student learning outcomes after the implementation of the AIR model assisted by SPIN media, with the improvement category being at a moderate to high level based on the N-Gain score. Student responses to learning also show a very positive category. The novelty of this study lies in the integration of the AIR model with IT-based SPIN media that is designed interactively, so that it can improve students'